Scientific metaphysics - Ross, Don, 1962-; Ladyman, James, 1969-; Kincaid, Harold, 1952- (Oxford : Oxford University Press, 2013)
Original essays by leading philosophers of science explore the question of whether metaphysics can and should be naturalised - conducted as part of natural science. They engage with a range of approaches and disciplines to argue that if metaphysics is to be capable of identifying objective truths, it must be continuous with and inspired by science.
Description based on online resource; title from home page (viewed on Dec. 20, 2012).
Includes bibliographical references and index.
Keywords: Metaphysics; Philosophy and science